An Investigation into the Relationship Between Musical Imagery and Anxiety. (September 2022) - Ulor, Michelle; Bailes, Freya; O'Connor, Daryl B.
Imagining music in the mind's ear is common in everyday life and is characterised by individual differences in who is likely to experience involuntary musical imagery. Research has explored the relationship between musical imagery and mental health (e.g., obsessive compulsive disorder); however, little is known about the relationship between anxiety and musical imagery. The current study investigated the associations between these two variables. 432 participants completed a cross-sectional, online survey, measuring trait anxiety, depression, musical imagery experience, the controllability of unwanted thoughts, and aspects of sleep. Positive associations were found between trait anxiety and the frequency, negative valence and perceived helpfulness of involuntary musical imagery, and the amount of music imagined whilst trying to sleep. Trait anxiety did not correlate with the controllability of auditory imagery. These findings provide a clearer understanding of musical imagery's relationship with anxiety and have implications for using voluntary musical imagery to reduce anxiety.